PENGEMBANGAN MEDIA AUGMENTED REALITY (AR) DALAM PEMBELAJARAN IPAS MATERI BAGIAN TUMBUHAN DAN FUNGSINYA PADA SISWA KELAS IV SD NEGERI 2 LENEK DAYA - Ratnawati; Arif Rahman Hakim; Husnul Mukti (STKIP Subang, 2024)
This study aims to develop Augmented Reality (AR) media in science learning onplant parts and their functions for fourth grade students of SD Negeri 2 Lenek, andto determine the level of validity of Augmented Reality (AR) learning media. Thisstudy uses the ADDIE development model which consists of 5 stages, namelyanalyze, desigh, deployment, implementation and evaluation. This study wasconducted on fourth grade students of SD Negeri 2 Lenek with 19 students. Theinstruments used in this study were the validation sheet of display experts, materialexperts, observation sheets, and student response questionnaires. The results ofthe validation test by display experts with a total score of 57 were in the range ofscores 51 63 with the category